Study Regarding The Influence Of Root Filling And Coronal Restoration In Chronic Apical Periodontitis: Prevalence And Severity - Cristian Giuroiu; Mihaela Sălceanu; Anca Melian; Claudiu Topoliceanu; Tudor Hamburda; Liana Aminov; Maria Vataman (Romanian Dental Association for Education, 2013)
Aim of the study The study aimed to determine the influence of root filling and coronal restorations quality on prevalence and severity of chronic apical periodontitis (CAP). Materials and method The study was performed on 126 patients (age 20-50), with a total number of 299 teeth with finished endodontic treatments and amalgam and composite resins restorations. The assessment of root fillings was performed on periapical radiographs and coronal restorations were assessed using clinical examination and byte-wing radiographs. The periapical status was analysed using P.A.I. indices. Results The study proves the high prevalence of chronic apical periodontitis (73.6%). High prevalence of C.A.P. (94.1%) and P.A.I. indices (4.06) are present for teeth with coronal restoration with poor marginal integrity and short root fillings. Conclusions Both the quality of the coronal restoration and the quality of the root filling (length and density) are correlated with the presence and severity of chronic apical periodontitis.